Language skill development in children with cochlear implants and the impact of age at switch-on. (2nd January 2023) - Hand, Lauren Sophie; Liu, Charlotte Ka Yun; Hardman, Gemma; Mahon, Merle
ABSTRACT: Deaf and hard-of-hearing (DHH) children with cochlear implants (CwCIs) constitute a heterogeneous population. A multitude of factors influence their spoken language development. There is evidence that CwCIs follow similar trajectories in language development as typically developing (TD) children but there is a lack of research on specific types of skills. This study aimed to (1) map the trajectory of receptive and expressive language skill development of a representative group of CwCIs and (2) evaluate the impact of age at switch-on (ASO) on skill development. This paper presents a detailed analysis of the language outcomes of 44 CwCIs with ASO between 11 and 45 months ( M = 26.02 SD = 8.31). These children were tracked for the first two years following implantation. Clustered bar charts were used to compare specific types of skills acquired by CwCIs with ASO ≤2 years versus >2 years. The results suggest that CwCIs generally acquire receptive and expressive language skills along a similar sequence to TD children, but there is individual variability relating to specific skills. However, the language outcomes of CwCIs are ultimately the result of a complex interplay of demographic variables.